Australian internet policy - Angela Daly; Julian Thomas (Internet Policy Review, 2017)
This special focussing on internet policy in Australia provides a snapshot of developments on various topics (access, privacy, censorship) as a means of understanding better the state of play in Australia, and also how this compares to internet policy in other parts of the world, especially Europe and North America. Given changing geopolitics, the influence of internet policy in the rest of the Asia Pacific through vehicles such as the Regional Comprehensive Economic Partnership (RCEP) may become increasingly important in Australia in the coming years. This leaves Australia, and its internet policy, at a crossroads, which may reflect broader dynamics in internet policy internationally, and makes this an interesting time in which to explore what is happening in this particular country.
Keywords: 300; Australia; Internet policy; Privacy